1988
DOI: 10.1126/science.3175624
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression of PDGF, TGF-α, and TGF-β Genes in Preimplantation Mouse Embryos

Abstract: Control of growth and differentiation during mammalian embryogenesis may be regulated by growth factors from embryonic or maternal sources. With the use of single-cell messenger RNA phenotyping, the simultaneous expression of growth factor transcripts in single or small numbers of preimplantation mouse embryos was examined. Transcripts for platelet-derived growth factor A chain (PDGF-A), transforming growth factor (TGF)-alpha, and TGF-beta 1, but not for four other growth factors, were found in whole blastocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
262
0
4

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 684 publications
(272 citation statements)
references
References 28 publications
6
262
0
4
Order By: Relevance
“…Both PDGF-A and PDGFar have been detected in pre-implantation mouse blastocyst and early embryos by RNA protection analysis. In contrast, the PDGFpr was not found until later, day 7.5 of gestation (Rappolee et al, 1988;Mercola et al, 1990). These findings suggest that the PDGF-A ligand and a receptor might be important in early embryonic development, while the p receptor is involved in later events.…”
Section: Introductionmentioning
confidence: 78%
“…Both PDGF-A and PDGFar have been detected in pre-implantation mouse blastocyst and early embryos by RNA protection analysis. In contrast, the PDGFpr was not found until later, day 7.5 of gestation (Rappolee et al, 1988;Mercola et al, 1990). These findings suggest that the PDGF-A ligand and a receptor might be important in early embryonic development, while the p receptor is involved in later events.…”
Section: Introductionmentioning
confidence: 78%
“…For a review of other growth factors in preimplantation development, see Rappolee et al [ 19901. Cleavage stage embryos from the 4 cell to blastocyst stage transcribe and translate the mRNA of three members of the TGF-f3 family [Rappolee et al, 1988;Paria et al, 19921. Embryos from the 8-cell stage bind TGF-f3s and express all three classes of TGF-P binding proteins or receptors.…”
Section: Other Growth Factors In Prel Mplantation Developmentmentioning
confidence: 99%
“…Several types of growth factors can influence preimplantation development in vitro, but this merely illustrates the presence of an active receptor rather than the necessity for the growth factor for development. Cytokines are involved in the latter stages of the pre-or peri-implantation embryo as the embryo meets the challenge of the mother's Rappolee et al, 1988Rappolee et al, 1988Dardik et al, 1992Rappolee et al, 1988Rappolee et al, 1988Rappolee et al, 1988Rappolee et al, 1990Rappolee et al, 1990Rizzino, 1985Rappolee et al, 1990Rappolee et al, 1990Rappolee et al, 1990Rappolee et al, 1992Rappolee et al, 1988Rappolee et al, 1988Paria et al, 1992Palmieri et al, 1992aPalmieri et al, 1992aPalmieri et al, 1992a Murray et al, Murray et al, 1990 immune system. Studies such as these are the focus of this essay.…”
mentioning
confidence: 99%
“…It has been suggested that these factors play important roles in preimplantation embryonic development and subsequent implantation [3]. Successful implantation requires embryo-uterus interactions that are only initiated when embryonic development is synchronized with the preparation of a receptive uterine state.…”
Section: Introductionmentioning
confidence: 99%